2020
DOI: 10.1213/ane.0000000000005145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perioperative Active Body Surface Warming Systems on Analgesic and Clinical Outcomes: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: BACKGROUND: Inadvertent perioperative hypothermia is a common complication of surgery, and active body surface warming (ABSW) systems are used to prevent adverse clinical outcomes. Prior data on certain outcomes are equivocal (ie, blood loss) or limited (ie, pain and opioid consumption). The objective of this study was to provide an updated review on the effect of ABSW on clinical outcomes and temperature maintenance. METHODS: We conducted a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 77 publications
1
28
0
1
Order By: Relevance
“…This is important, especially in orthopaedic surgery, where lesions of small osseous vessels that cannot be coagulated mainly contribute to perioperative blood loss [67]. Active body-surface warming and maintenance of normothermia can reduce blood transfusions (odds ratio 0.6) in non-cardiac surgery [68].…”
Section: Blood Loss and Transfusion Requirementmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important, especially in orthopaedic surgery, where lesions of small osseous vessels that cannot be coagulated mainly contribute to perioperative blood loss [67]. Active body-surface warming and maintenance of normothermia can reduce blood transfusions (odds ratio 0.6) in non-cardiac surgery [68].…”
Section: Blood Loss and Transfusion Requirementmentioning
confidence: 99%
“…Hypothermia-associated surgical site infections may increase the length and overall cost of the postoperative in-hospital stay [74]. A recent metanalysis found that active body-surface warming reduces wound infections with an odds ratio of 0.3 (95% CI, 0.2-0.7) after non-cardiac surgery [68]. Perioperative hypothermia affects the immune system, and consequently the host defence against pathogens, in various ways.…”
Section: Surgical Site Infections and Complicationsmentioning
confidence: 99%
“…The occurrence of inadvertent perioperative hypothermia is well known in surgery, where it is associated with increased complication rates (e.g., wound infections, shivering, need for blood transfusions, and cardiovascular complications) [22,23]. In the randomized SIESTA trial, temperature disturbances (i.e., hyperthermia of >37.2°C or hypothermia of <36°C) were associated with performance of EVT under general anesthesia [12].…”
Section: Ta B L E 2 Multivariate Analysis For Favorable Outcome and M...mentioning
confidence: 99%
“…2 Core temperature is tightly regulated, and even mild perioperative hypothermia is associated with adverse consequences. [3][4][5][6][7][8][9] The lack of accurate, user-friendly temperature monitoring devices is a known barrier to optimum thermoregulation practices across the multidisciplinary perioperative pathway. 10,11 International guidelines specify that temperature measurement is conducted at specific, regular intervals, using a consistent device.…”
Section: Introductionmentioning
confidence: 99%